2017
DOI: 10.4028/www.scientific.net/kem.728.117
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of (Mn<sub>x</sub>Co<sub>1-x</sub>)<sub>3</sub>O<sub>4</sub> Coated Stainless Steel AISI 430 by Electrodeposition with AC+DC Signals

Abstract: A ferritic stainless steel (FSS) AISI 430 coated by (MnxCo1-x)3O4 spinel has been intensively studied for its potential in application as an interconnect of a solid oxide fuel cell (SOFC). In this study, in order to develop fabrication of (MnxCo1-x)3O4 coatings, Mn-Co coatings on AISI 430 by an electrodeposition technique was adopted. The electric direct current (DC) and alternative current (AC) modulated DC (AC+DC) signals were utilized to drive voltage levels for electrodeposition. By varying the duty of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Münz et al [26] reported an improvement in the anti-corrosion properties of Zn/Mn multilayer coatings and resulted that the formation of Zn-Mn and γ-Mn 2 O 3 components suppressed oxygen reduction at the cathode, slowing the corrosion process. In another work by Wiman et al [27], the effect of the current types (AC, DC, or AC + DC) on the phase structure, surface morphology, and anti-corrosion properties of electrodeposited Mn-Co coatings on AISI 430 was investigated. Their results indicated that the (Mn x Co 1−x ) 3 O 4 coating exhibited the protective effect against oxidation of the steel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Münz et al [26] reported an improvement in the anti-corrosion properties of Zn/Mn multilayer coatings and resulted that the formation of Zn-Mn and γ-Mn 2 O 3 components suppressed oxygen reduction at the cathode, slowing the corrosion process. In another work by Wiman et al [27], the effect of the current types (AC, DC, or AC + DC) on the phase structure, surface morphology, and anti-corrosion properties of electrodeposited Mn-Co coatings on AISI 430 was investigated. Their results indicated that the (Mn x Co 1−x ) 3 O 4 coating exhibited the protective effect against oxidation of the steel.…”
Section: Introductionmentioning
confidence: 99%
“…Journal of Theoretical and Applied Physics (2020) 14:[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] …”
mentioning
confidence: 99%